The Effect of Personalized Advertising on Attitude towards Advertising and Click- Through Rate - Nurhidayah, Siti; Dirgantara, I Made Bayu (LifeSciFi, 2025)
This study aims to analyse the effect of Personalized Advertising on Attitudes towards Advertising and Click-Through Rate, with Privacy Concerns as a mediating variable, focusing on AXIS card users in Semarang City. The research addresses the challenge faced by AXIS Company, a telecommunications service provider, in attracting and retaining users amidst intense market competition. The population for this study comprises AXIS Provider card users in Semarang City, with a sample size of 160 individuals who have made at least one purchase through the AXISNET application. A quantitative approach was employed, utilizing the SEM- PLS method with Smart PLS version 4 software. The analysis included testing the validity and reliability of measurement instruments and conducting hypothesis testing through bootstrapping procedures. The findings reveal that personalized advertising significantly and positively influences attitudes towards advertising and the click- through rate, with privacy concerns acting as a significant mediating variable. These results highlight the importance of privacy concerns for users and the effectiveness of personalized advertising in enhancing user attitudes towards advertising and increasing the click-through rate. This study underscores the need for effective marketing strategies that address privacy concerns to improve advertising outcomes for AXIS Company.